The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/foods10030654
|View full text |Cite
|
Sign up to set email alerts
|

Can Chemical Analysis Predict Wine Aging Capacity?

Abstract: Oxidation is the limiting factor in wine aging, and recently some famous wines have exhibited unexpected premature oxidation. Antioxidant assays may provide a means to assess a wine’s aging potential by measuring its capacity to chemically reduce reagent components. Correlations between antioxidant activity and wine components have the highest value with flavanols, notable for their catechol and phloroglucinol moieties. Both FRAP and DPPH based methods respond strongly to catechol groups, but these functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As mentioned above, we speculated that the significantly lower contents of amino acids in wines aged with new oak barrels found in this study could possibly be linked to the higher degree of oxygenation taking place in new barrels because of their higher wood porosity [ 24 ]. To support this assumption, it has been documented that oxidative reactions of phenolic substances during barrel aging yields quinones which can actively react with several nucleophiles, such as tannins, flavan-3-ols and amino acids, resulting in the reduction of these compounds in the finished wines [ 39 ]. Also, oxidative effects on the degradation of sulfur-containing amino acids, such as phenylalanine and methionine, in wines have been reported [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, we speculated that the significantly lower contents of amino acids in wines aged with new oak barrels found in this study could possibly be linked to the higher degree of oxygenation taking place in new barrels because of their higher wood porosity [ 24 ]. To support this assumption, it has been documented that oxidative reactions of phenolic substances during barrel aging yields quinones which can actively react with several nucleophiles, such as tannins, flavan-3-ols and amino acids, resulting in the reduction of these compounds in the finished wines [ 39 ]. Also, oxidative effects on the degradation of sulfur-containing amino acids, such as phenylalanine and methionine, in wines have been reported [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many review articles have categorized polyphenols in wine (Figure 1) (Cataldo et al., 2023; Merkyte et al., 2020). The antioxidant capacity of red wines (stored at 10°C in the dark) was analyzed by Ferric reducing antioxidant power assay (FRAP) and DPPH• assay, and the results showed good correlation between antioxidant capacity and total flavanols content (527 mg L −1 catechin) of red wines, with R 2 = 0.842 and 0.786, respectively; moreover, sensory testing and the results from potentiometric titration assay were highly correlated (R 2 = 0.8869), therefore, it is suggested that wine aging capacity can be predicted by polyphenols (Waterhouse & Miao, 2021). The antioxidant capacity of red wines is significantly higher than white wines because red wines have higher amounts of polyphenols.…”
Section: Polyphenolsmentioning
confidence: 99%
“…During wine aging, oxidation is the crucial limiting factor, and premature oxidation is a possible problem and potential risk that can occur during wine aging, causing cloudiness, yellowing and browning, and loss of positive aromas. Therefore, aging capacity (potential) is an essential factor in wine quality [39]. Traditionally, aging potential (aging capacity) is a concept and positive sensory definition used by wine tasting experts to evaluate a wine's ability to retain its quality and typicity during aging.…”
Section: Macro-classification Of Red Wine Colormentioning
confidence: 99%